Muhammadiyah Diaspora Diplomacy in Protecting Indonesian Migrant Workers in Malaysia - Anam, Muhammad Zahrul; Munir, Ahmad Nubail; Hidayat, Radiva Rusyda (Jurnal Hubungan Internasional, 2022)
Malaysia is one of the main destination countries for Indonesian migrant workers (PMI). Although their contribution is large for developing the two countries, PMI, especially women workers in the informal sector, still experience violence and discrimination. Protection efforts through diplomacy between the two countries have not effectively protected PMI in Malaysia without involving non-state actors. Muhammadiyah as a religion-based non-state actor, has been heavily involved in alleviating the problems of vulnerable groups, including PMI in Malaysia. However, only a few studies specifically discuss Muhammadiyah diplomacy’s role in protecting PMI in Malaysia. This article aims to explain the role of Muhammadiyah diaspora diplomacy toward protecting PMI in Malaysia as part of the Muhammadiyah internationalization agenda through Pimpinan Cabang Istimewa Muhammadiyah (PCIM). The data used in this article came from secondary data that explored the frequency of reporting about PCIM Malaysia activities in four selected online media. The media included two national media, Antara and Tribune, and two Islamic media, Suara Muhammadiyah and Republika. This article also utilized primary data from interviews with PCIM and Pimpinan Cabang Istimewa ‘Aisyiyah Malaysia, which were analyzed using NVivo 12 software. This article argued that PCIM Malaysia carried out diaspora diplomacy to PMI in Malaysia through mediation, advocacy, representation, and Muhammadiyah internationalization.